(untitled) (Revue El-Wahat pour les Recherches et les Etudes, 2020)
The price is defined in public works contracts as the financial consideration that the contracting interest is obligated to pay to the contractor for the services it is committed to accomplishing for its benefit, and given the close connection between the public works contract and the idea of public money as well as the rights of the public treasury, the legislator has organized several solutions that enable the administration to implement its project without harming the contractor By authorizing it to disburse amounts in the form of an advance, or a payment under the account, or a settlement on the account balance by way of temporary or final payment of the price stipulated in the deal after the full execution of the works. Key words - Public works contract, price, advance, account, settlement.